The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/00037028211062239
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Design and Implementation of an In-Line Near-Infrared Probe Using Computational Fluid Dynamics for Measurement of Non-Newtonian Fluids

Abstract: Process analytical technology (PAT) has developed significantly since its introduction in pharma where many in situ analytical probes and measuring devices are now commercially available, replacing the use of off-line quality control measurements that are typically laborious and time intensive. The use of PAT instrumentation should not interfere with the process itself and subsequently should have no effect on the product whilst measuring representative samples. Implementation of these devices is typically arb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…PAT monitoring is governed by the same principles as those defined by the theory of sampling. ,, Although the literature shedding light on the impact of the position of PAT probes used to monitor liquids is limited, it is well-recognized that the lack of mixing and poor choice of probe angle and depth might lead to spatial heterogeneity of suspended particles in stirred crystallizers/tanks. ,, Particularly, it has been demonstrated that the signal quality for probe designs with flow-through gaps/slids/cells, as employed in the CCSA (Figure S3 in the Supporting Information), , strongly depends on the hydrodynamic conditions influenced by the probe orientation, angle, and immersion depth. , Arbitrary placement of PAT probes can lead to stagnant liquid accumulating in the probe gaps/slids/cells resulting in nonrepresentative and fluctuating measurements of the bulk properties . In the present work, it was attempted to align the cell of the CCSA probe along the liquid motion in the crystallizer (Figure S3 in the Supporting Information) to permit unrestricted flow through the measuring cell without claiming to have achieved optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PAT monitoring is governed by the same principles as those defined by the theory of sampling. ,, Although the literature shedding light on the impact of the position of PAT probes used to monitor liquids is limited, it is well-recognized that the lack of mixing and poor choice of probe angle and depth might lead to spatial heterogeneity of suspended particles in stirred crystallizers/tanks. ,, Particularly, it has been demonstrated that the signal quality for probe designs with flow-through gaps/slids/cells, as employed in the CCSA (Figure S3 in the Supporting Information), , strongly depends on the hydrodynamic conditions influenced by the probe orientation, angle, and immersion depth. , Arbitrary placement of PAT probes can lead to stagnant liquid accumulating in the probe gaps/slids/cells resulting in nonrepresentative and fluctuating measurements of the bulk properties . In the present work, it was attempted to align the cell of the CCSA probe along the liquid motion in the crystallizer (Figure S3 in the Supporting Information) to permit unrestricted flow through the measuring cell without claiming to have achieved optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
“…23,37,74−76 Particularly, it has been demonstrated that the signal quality for probe designs with flow-through gaps/slids/ cells, as employed in the CCSA (Figure S3 in the Supporting Information), 37,38 strongly depends on the hydrodynamic conditions influenced by the probe orientation, angle, and immersion depth. 24,73 Arbitrary placement of PAT probes can lead to stagnant liquid accumulating in the probe gaps/slids/ cells resulting in nonrepresentative and fluctuating measurements of the bulk properties. 73 In the present work, it was attempted to align the cell of the CCSA probe along the liquid motion in the crystallizer (Figure S3 in the Supporting Information) to permit unrestricted flow through the measuring cell without claiming to have achieved optimized conditions.…”
Section: Solvent-mediated Polymorphic Phase Transformation Of Ffa Iii...mentioning
confidence: 99%
See 3 more Smart Citations